environmental monitoring, cartography, image processing, sub-saharan Africa, R programming - Jan Krynski; Przemyslaw Dykowski; Walyeldeen Godah (Advances in Geodesy and Geoinformation, 2023)
The article presents the reviewed and summarised research activities of the Polish research groups on gravimetry and gravity field modelling in the period of 2019–2022. It contains the results of absolute gravity surveys for the maintenance of the international gravity reference level in Poland and Europe, and for geodynamic research with an emphasis on metrological aspects. It also contains relative gravimetry issues as well as the results of marine gravity surveys in the southern Baltic Sea. Non-tidal gravity changes were extensively investigated. Long-term gravity variations were monitored at the Borowa Gora Geodetic-Geophysical Observatory and in a few other locations in Poland. The contribution of gravimetric records to seismic studies was investigated. Temporal variations of the gravity field from GRACE (Gravity Recovery and Climate Experiment) and GRACE-FO (GRACE Follow-On) data, in particular, deformations of the Earth’s surface as well as temporal variations of heights, total water storage and groundwater storage were investigated. Moreover, GRACE-based products and the performance of monthly Global Geopotential Models (GGMs) were a subject of research. GGMs developed in last years were evaluated. The research on developing new approaches in geoid modelling and their validation was conducted. New regional and local geoid models were determined for Poland and Ethiopia. The use of different techniques for estimating the absolute sea level at sites of the selected network in the Baltic Sea was investigated.